Rancang Bangun Aplikasi Penjadwalan Produksi pada PT Bina Megah Indowood - Wiratama, Dedy Armada; Supriyanto, Antok; Wibowo, Januar (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT Bina Megah Indowood private companies that moves in wood manufacture with the main product wood flooring and wood decking .Maximum firm production capacity when is 700 container per year but in 2015 total firm production of 600 container with the number of refusal order of about 20 container this was caused because methods used by companies are not yet optimal .The company uses the least work remaining ( lwr ) with priority given in the work have the number of processing left still needed to be done at least .This study attempts to help select company of a method of the best in make the production by comparing five method .Fifth this method is fcfs , edd , spt , lpt and lsf .The result of research this is the report scheduling production permesin and reports scheduling production permesin by the application of bebbasis desktop .The results of the tryouts application obtained value of 93 % and hasi.